Clinical Evidence and Proposed Mechanisms of Sodium–Glucose Cotransporter 2 Inhibitors in Heart Failure with Preserved Ejection Fraction: A Class Effect? - Brent Deschaine; Sahil Verma; Hussein Rayatzadeh (Cardiac Failure Review)
Effective treatment for heart failure with preserved ejection fraction (HFpEF) is an unmet need in cardiovascular medicine. The pathophysiological drivers of HFpEF are complex, differing depending on phenotype, making a one-size-fits-all treatment approach unlikely. Remarkably, sodium–glucose cotransporter 2 inhibitors (SGLT2is) may be the first drug class to improve cardiovascular outcomes in HFpEF. Randomised controlled trials suggest a benefit in mortality, and demonstrate decreased hospitalisations and improvement in functional status. Limitations in trials exist, either due to small sample sizes, differing results between trials or decreased efficacy at higher ejection fractions. SGLT2is may provide a class effect by targeting various pathophysiological HFpEF mechanisms. Inhibition of SGLT2 and Na+/H+ exchanger 3 in the kidney promotes glycosuria, osmotic diuresis and natriuresis. The glucose deprivation activates sirtuins – protecting against oxidation and beneficially regulating metabolism. SGLT2is reduce excess epicardial adipose tissue and its deleterious adipokines. Na+/H+ exchanger 1 inhibition in the heart and lungs reduces sodium-induced calcium overload and pulmonary hypertension, respectively.